Ichthyofauna of Aceh River, Aceh Province, Indonesia. (December 2018) - Dekar, M; Sarong, M A; Batubara, A S; Muchlisin, Z A
Abstract: Information on fish fauna in Aceh Besar District, Aceh Province, Indonesia is scared; hence, the objectives of the present study was to documented and to the analysis of the fish fauna in Aceh Besar District, Indonesia. The sampling was conducted from May 2016 to February 2017 at seven sampling locations around Aceh Besar District (Inong River, Seulimum River, Kreumireu River, Jreu River, Daroy River, and Naeuk River) and Banda Aceh City (the Aceh River Mouth at Lampulo and Alue Naga). The fish samples were caught using several fishing gears such as; casting nets, gillnets, handnet, and fish trap. The fish samples were taxonomically identification using Kottelat et al. (1993) and Nelson (1994). The results showed that a total of 250 individual of fishes belongs to 44 species, 34 genera and 25 families were recorded during the study. Oreochromis niloticus the alien species was widely distributed in Aceh Besar and Banda Aceh waters followed by Gerres filamentosus, Channa sariata and Puntius brevis .